PROFESSIONAL EXAMINATIONS. - Chamberlain, Henry T.; Chamberlain, John H.; Mautz, R. K. (The Accounting Review, 1959)
This article presents accounting problems which were prepared by the Board of Examiners of the American Institute of Certified Public Accountants (C.P.A.) and were presented as the first half of the C.P.A. examination in accounting practice on November 5, 1958. One of the problems says that Lynn and Kay, architectural designers and interior decorators, combined May 1, 1958, agreeing to share profits, Lynn, two-thirds, Kay, one-third. Lynn contributed furniture and fixtures, $3,000, and cash $2,000, Kay contributed cash, $500. They plan to submit monthly bills and make the following arrangements with their clients, the salaries of draftsmen and shopper who are paid on an hourly basis, shall be billed to clients at the hourly rate for time spent on each job, plus 125% for overhead and profit and plus ft% for all payroll taxes. Partners' time on jobs shall be billed at $10 an hour. A 10% service fee shall be charged on purchases of furniture, drapes, etc., installed on the jobs. There will be no service fee on taxis, telephone and other expenses identifiable to jobs and charged to clients.